The COVIDTrach prospective cohort study on outcomes in 1982 tracheostomised COVID-19 patients during the first and second UK pandemic waves - Matthew Haywood; Gareth Ambler; Ciara Walker; Asit Arora; Tony Jacob; Anne G. M. Schilder; Nick Hamilton; COVIDTrach Collaborators (Scientific Reports)
Abstract COVIDTrach is a UK-wide, prospective cohort study evaluating tracheostomised COVID-19 patient outcomes and operator disease transmission. Early in the pandemic controversy surrounded optimal timing of tracheostomy insertion, however meta-analyses have since addressed this uncertainty. We report on our cohort’s data and outcomes to help inform the management of this disease and compare our findings to the literature. Our inclusion criteria were COVID-19 patients aged ≥ 18 undergoing tracheostomy following invasive ventilation. We recorded relevant characteristics, clinical parameters, intra-operative details and outcome data. Predictors for mortality and time to ventilatory wean were determined. Among 1982 patients, there was a 21% post-tracheostomy mortality and median intubation to tracheostomy time of 15 days (IQR 11–21). The median time to successful ventilatory wean post-tracheostomy was 12 days (IQR 7–20). Advancing age, greater FiO2 and PEEP requirements and inotrope or anticoagulant use were associated with increased mortality (p < 0.05) and time to wean success (p < 0.01). Higher CRP predicted increased mortality (p < 0.05), while NIV use and extended pre-tracheostomy ventilation predicted prolonged wean time (p < 0.01). The death risk for tracheostomy performed ≤ 7 or ≥ 14 days of ventilation was equivocal (OR 1.01, 95% CI [0.37–2.72]) but lower between 8 and 14 days (OR = 0.64, 95% CI [0.47–0.86]) (p = 0.01). Eight operators tested positive within two weeks of performing a tracheostomy. Our mortality rates were similar to cohort studies but lower than early versus late tracheostomy designs. In contrast to the literature, we found reduced mortality when tracheostomy was performed 8–14 days post-intubation, with more favourable wean time and wean and decannulation rates.